Gender and Language: A Review on the Use of Language by Male and Female University Students - Gökçen Kara (Akademik Dil ve Edebiyat Dergisi, 2026)
Language is socially constructed and used as a powerful means of repression, and language has an important place in the struggle of male/female classes, which is the biggest class struggle. Since gender is an ideology, its language is constructed both socially and universally. Since the dominant ideology was patriarchal, the woman remained within the framework of the discourse determined by patriarchy. This patriarchal society makes the language, the object of man. This order that makes women passive takes them under the dominance of a language that is shaped by men. Based on this order, feminist linguists pointed out that women had to live in a language that was produced by men, which prevented them from expressing themselves. Language is such a strong and deep structure that even when women start to take part in the public arena, They to do it through a male dominant language.This study aims at investigating gender differences in language. The study consists of two parts: theory and practice. The first section covers gender and language theories. In the second section, the speech analysis method was used to determine the differences between female and male language. The participants, consisting of 16 university students, were divided into groups of 4 people and each group was interviewed separately. The evaluation of speech recordings is based on the work of Jennifer Coates. When the speech analysis data were examined, it was revealed that there were significant differences in speech between the female and male participants.